Gambaran Tingkat Pengetahuan Dan Perilaku Masyarakat Tentang Pemberantasan Sarang Nyamuk Di Banjar Dinas Dangin Pura Desa Panji Sukasada Buleleng - Agung Sintha; Putu Intan Daryaswanti (Bali Health Published Journal, 2021)
Background: Dengue hemorrhagic fever is one of the population's health issues in Indonesia, with an increasing number of sufferers as the disease spreads. The cases rose dramatically in Panji Village, with a significant spike in cases per year. Dengue hemorrhagic fever transmission is inextricably linked to the residents' experience and behavior. Mosquito Nest Eradication is the most reliable, safe, and cost-effective method of eliminating dengue fever vectors. The MNE Program must be complemented by increasing public awareness of dengue fever. Public awareness is needed since it is the first step in changing people's behavior. The aim of this study is to describe the community's level of knowledge and behavior regarding MNE in Panji Village. Method: This study is a descriptive study using univariate analysis. The overall selection of this study was 400 people from the community who were interviewed using a questionnaire. The inclusion criteria comprises any community member from Banjar Dinas Dangin Pura, who is 17 to 55 years old and can read and write. Meanwhile, people between the ages of 17 and 55 who are wandering, those with mental illnesses, and people with special needs are among the exclusion criteria. Results: The majority of the population in the Banjar Dinas Dangin Pura Panji Village was between the ages of 26 and 35 (46.7%), In terms of gender (224 people) (56%) were men, completed their high schools, with 229 people (57.3%), were working as farmers 158 individuals (39.4%). Most people in Banjar Dinas Dangin Pura Panji Village had inadequate knowledge as many as 249 individuals (62.3%), and had less behavior as many as 152 individuals (38%) towards MNE. Conclusion : The majority of people had a poor degree of awareness about MNE, and those on MNE had a poor degree of behavior.